Quality of nursing care and patient satisfaction in primary health care: integrated review - Bernardo, Deolinda; Lucas, Pedro (Millenium - Journal of Education, Technologies, and Health, 2021)
Introduction: The quality of nursing care (NC) has a strong impact on patient satisfaction (PS) and is an essential dimension of the nursing practice environment. Objectives: To analyze about PS with NC in Primary Health Care. Methods: Integrative literature review with 3 steps. 1) An initial search at CINHAL and MEDLINE. 2) A broader search, using the same keywords and search terms, in the remaining databases of the EBSCOHost platform. 3) Search the bibliographic references of the selected articles. The selected studies were from the period between 2009 and 2019. Results: Twenty studies were selected that report findings on the dimensions that make up the PS concept: art in care; technical or scientific quality; costs; physical and environmental organization; availability of professionals; continuity of care; and NC results. Conclusion: PS is described as the value and reaction to the nursing care they received. PS with NC is considered a fundamental indicator of the quality of nursing care.